The The Implementation Method of Bored Pile Foundation in the ARC 100 Construction Project, Gubeng, Surabaya: Inggris - Karlima Hutagaol; Petrus Hilman Situmorang; Pandya Fadil Munpintoro; Tarsim (CV. AFDIFAL MAJU BERKAH, 2025)
The substructure of bored pile foundations is one type of deep foundation commonly used in high-rise building construction, particularly in areas with low soil bearing capacity, such as the ARC 100 Gubeng Construction Project in Surabaya. Both primary and secondary data were collected through interviews with contractors and project service providers involved in the foundation work. Based on the observations conducted, the bored pile foundation work utilized the wet boring method using Zoomlion heavy equipment, beginning with the preparation stage, determination of foundation bore points, and site cleaning. This was followed by the installation of temporary casing, foundation hole drilling, reinforcement fabrication, reinforcement placement, and welding of reinforcement joints. Next, a slump test was performed on the concrete mix, followed by the installation of the tremie pipe, concrete casting, removal of the temporary casing, and final site cleaning. The bored pile foundation work for the ARC 100 Gubeng project in Surabaya was carried out in accordance with standard construction procedures. Any factors that could potentially hinder the work were promptly addressed. Furthermore, both the contractor and consultant agreed that workplace safety must always remain a top priority throughout the entire construction process. Keywords: Bored Pile Foundation, High-Rise Building, Temporary Casing